Immunogenic Domains and Secondary Structure of Escherichia coli Recombinant Secreted Protein Escherichia coli-Secreted Protein B - Caetano, Bruna Alves; Rocha, Letícia Barboza; Carvalho, Eneas; Piazza, Roxane Maria Fontes; Luz, Daniela (Frontiers in Immunology, 2017)
Several pathogenic bacteria are able to induce the attaching and effacing (A/E) lesion. The A/E lesion is caused by effector proteins, such as Escherichia coli-secreted protein B (EspB), responsible together with Escherichia coli-secreted protein D for forming a pore structure on the host cell, which allows the translocation of effector proteins. Different variants of this protein can be found in E. coli strains, and during natural infection or when this protein is injected, this leads to variant-specific production of antibodies, which may not be able to recognize other variants of this bacterial protein. Herein, we describe the production of a hybrid recombinant EspB toxin that comprises all known variants of this protein. This recombinant protein could be useful as an antigen for the production of antibodies with broad-range detection of EspB-bearing bacteria, or as an antigen that could be used in vaccine formulation to generate antibodies against different EspB variants, thereby increasing immunization potential. In addition, the recombinant protein allowed us to analyze its secondary structure, to propose the immunogenic regions of EspB variants, and also to characterize anti-EspB antibodies. Our results suggest that this hybrid protein or a protein composed of the conserved immunogenic regions could be used for a variety of clinical applications.